Effectiveness of Poster, Animated Video and Live Youtube on Knowledge of Metabolic Syndrome and Sugar, Salt and Fat Consumption Recommendations (GGL) - Kikan Yoganika Kausa; Ratih Kurniasari (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Excessive consumption of sugar, salt and fat in society due to lack of knowledge is increasing from year to year and causing high incidence of metabolic syndrome. Efforts to handle it can be done through nutrition education. Objective: The purpose of this study was to determine the effectiveness of the influence of the media namely posters, animated videos and Live Youtube on knowledge of metabolic syndrome and recommendations for consumption of sugar, salt and fat in women of the Al-Mutaqqin taklim assembly. Method: The type of research is Quasi Experiment with Pretest – Posttest design group. A sample of 45 mothers were determined by purposive sampling technique. Knowledge is measured with a questionnaire instrument. Data were analyzed by using the Paired T Test and One Way Anova test using PostHoc and Tukey analysis. Result: . It was found that there was an effect of nutrition education with the three media on knowledge of metabolic syndrome and recommendations for consuming GGL with p<0.005. For Metabolic Syndrome Knowledge, Poster with live youtube with sig. of 0.027 <0.05 then H0 is rejected. Live Youtube with posters with sig numbers. of 0.027 <0.05 then H0 is rejected. It can be concluded that the group that was given the YouTube live media was better than the poster media and animated video media with the result that the knowledge of Metabolic Syndrome at the posttest increased more than the other media. Conclusion: The conclusion of this study is that all media have an effect on increasing knowledge about metabolic syndrome and recommending the consumption of sugar, salt and fat. The most influential media is YouTube live media because of its advantages that other media don't have, namely interaction.